Avaliação do potencial eólico em microescala de cascavel e região - Sato, Mireille (2015)
The global energy scenario points to the need for alternative energy sources, given the dependence on finite fossil fuels and highly polluting. Among the clean energy resources, there is the wind, inexhaustible resource that gives the transformation of the kinetic energy contained in wind into mechanical energy through a turbine The global wind power available is around 53.000 TWh /year , since in terms of wind potential 143.000 MW fit the Brazilian wind potential and of this total 1.360 MW give the state of Paraná, locus of this study . Within this context , this study aims to determine the wind potential for microgeneration and minigeneration Cascavel and region, and has the following specific objectives determine the average speed of winds and annual seasonally each municipality target of this investigation, determining the annual wind potential of each target district this investigation depending on the heights of the tower 10 , 25 and 40 meters, analyzing the annual energy required by a residence and a water pump comparing it with the annual energy generated by the wind power system for all municipalities in question and the type of wind development more suitable for the use of wind power available for each target municipality of this investigation.The methodology is to develop histograms of wind speed in the municipalities of Assis Chateaubriand, Cascavel, Foz do Iguaçu, Guaíra, Palotina, Santa Helena, São Miguel do Iguaçu and Toledo , as well as describe the wind speed variable flow by Function Weibull probability density , determine the wind potential and finally achieve the required and generated energy simulation . At the end of the work can be concluded that only the city of Cascavel has a good wind potential .